Level of Knowledge of PKK Mothers in RW VI, Krapyak Village Regarding the Use of Anti-Aging Skincare - Natasha Shella Putri; Eny Widhia Agustin; Erna Setyowati; Adhi Kusumastuti (Journal for Quality in Public Health, 2025)
Aging is an unavoidable nature. In RW VI, Krapyak Village, most mothers have experiencing the aging period and have skin aging problems, but have not focused on using anti-aging skincare. The purpose of this study was to determine the level of knowledge of PKK mothers in RW VI, Krapyak Village regarding the use of anti-aging skincare. This study used a descriptive method with a quantitative approach and a cross-sectional survey design. The subjects of this study were PKK mothers in RW VI, Krapyak Village. The variables in this study were the level of knowledge of PKK mothers in RW VI, Krapyak Village regarding the use of anti-aging skincare. Data collection techniques used questionnaires, observation, and documentation. Data analysis techniques used descriptive percentages. The results showed that the best knowledge was in the 30-40 year age group (84.6%), the S3 education group (100%), and the private employment group (85.7%). The conclusion of this study is that the knowledge of PKK mothers in RW VI, Krapyak Village in using Anti-Aging Skincare is in the good category. Based on the research results, it is hoped that it can provide additional information to increase knowledge about skincare and skin aging.